Mechanical properties of poly–propylene reinforced with Argan nut shell aggregates: Computational strategy based microstructures. (June 2020) - El Moumen, A.; N'Guyen, F; Kanit, T.; Imad, A.
Abstract: This paper aims at developing 3D numerical simulations of the mechanical properties of polymer composites based on the aggregates of argan shell. The microstructure is made up of two phases, corresponding to the Poly–Propylene PP matrix and the natural aggregates. Due to the grinding operation of agran shell during the manufacturing process, the aggregates shapes, crushed aggregates, greatly vary with their surfaces. The majority of published works used the spherical or ellipsoidal forms in order to study numerically the mechanical behavior of such composites, because of the inherent simplification in algorithm formulations. However, real microstructures of these composites based simple microscopic, show that the shape of aggregates does not takes a spherical form, but a polyhedral form. In this study, the microstructure is described and modeled as a combination of Poisson polyhedral and PP matrix. In the numerical model, the obtained aggregate morphology is similar to that of many argan shell powders often used as reinforcement of the PP matrix. This technique allows generating models with different reinforcement volume fractions up to 28%. The numerical homogenization technique is used to estimate the mechanical properties of these composites. The set obtained numerical results with 3D polyhedral model are compared with the pertinent experimental data and analytical models reported in the literature. The performance of the most used micromechanical schemes used in predicting the effective elastic properties of biocomposites was discussed.